2012
DOI: 10.1016/j.arthro.2012.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results After SLAP Repair: A 5-Year Follow-up Study of 107 Patients With Comparison of Patients Aged Over and Under 40 Years

Abstract: Level IV, therapeutic case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…No significant difference in the clinical outcomes was observed between patients who underwent non-operative treatment and surgical repair. Furthermore, in terms of patient satisfaction, the average VAS score for satisfaction in patients who underwent non-operative treatment was 8.3, which was comparable with the 85-90 % satisfaction rate in young athletes who were treated with SLAP repair [12,21,22]. Hence, the satisfaction rates after non-operative treatment are comparable to those after surgical treatment in athletes.…”
Section: Discussionsupporting
confidence: 63%
“…No significant difference in the clinical outcomes was observed between patients who underwent non-operative treatment and surgical repair. Furthermore, in terms of patient satisfaction, the average VAS score for satisfaction in patients who underwent non-operative treatment was 8.3, which was comparable with the 85-90 % satisfaction rate in young athletes who were treated with SLAP repair [12,21,22]. Hence, the satisfaction rates after non-operative treatment are comparable to those after surgical treatment in athletes.…”
Section: Discussionsupporting
confidence: 63%
“…In that series, a failure rate of 38% was observed, with 28% of patients requiring revision surgery. Schroder et al [9] presented 102 patients treated by SLAP repair with resorbable tacks (Suretac; Acufex; Smith&Nephew) at a mean follow-up of 5 years. There were no significant differences between the results for patients 40 years of age or older and those under 40 years of age – which stands in contrast to the findings from Provencher et al [8] In our series, we operated on a total of 3 patients over 40 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Alpert et al 11) also concluded that arthroscopic repair of isolated type II SLAP lesions could yield good to excellent results in patients both older and younger than 40 years, and that there were no significant differences in functional scores, satisfaction level, or willingness to undergo the same surgical procedure again between the 2 groups. In a minimum 5-year followup study by Schrøder et al, 10) good long-term outcomes were achieved after repair of isolated SLAP lesions regardless of age or sex. Similar to these studies, [9][10][11] in the current study arthroscopic repair of isolated type II SLAP lesion yielded good functional outcome regardless of age, because the appropriate surgical indications, procedures, and postoperative rehabilitation were followed.…”
Section: Discussionmentioning
confidence: 99%
“…In a minimum 5-year followup study by Schrøder et al, 10) good long-term outcomes were achieved after repair of isolated SLAP lesions regardless of age or sex. Similar to these studies, [9][10][11] in the current study arthroscopic repair of isolated type II SLAP lesion yielded good functional outcome regardless of age, because the appropriate surgical indications, procedures, and postoperative rehabilitation were followed. Considering that postoperative stiffness is known to be a common complication after surgical repair of type II SLAP lesions, the current results of postoperative ROM, especially external rotation at 90˚ abduction, were satisfactory in both groups at the final follow-up, and the change in ROM did not differ significantly between the 2 age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation